Origin and characterization of small membranous vesicles present in the venom of Crotalus durissus terrificus. (15th September 2017) - Souza-Imberg, Andréia; Carneiro, Sylvia Mendes; Giannotti, Karina Cristina; Sant'Anna, Sávio Stefanini; Yamanouye, Norma
Abstract: Small membranous vesicles are small closed fragments of membrane. They are released from multivesicular bodies (exosomes) or shed from the surface membrane (microvesicles). They contains various bioactive molecules and their molecular composition varies depending on their cellular origin. Small membranous vesicles have been identified in snake venoms, but the origin of these small membranous vesicles in the venom is controversial. The aim of this study was to verify the origin of the small membranous vesicles in venom of Crotalus durissus terrificus by morphological analyses using electron microscopy. In addition, the protein composition of the vesicles was analyzed by using a proteome approach. The small membranous vesicles present in the venom were microvesicles, since they originated from microvilli on the apical membrane of secretory cells. They contained cytoplasmic proteins, and proteins from the plasma membrane, endoplasmic reticulum (ER), and Golgi membrane. The release of microvesicles may be a mechanism to control the size of the cell membrane of the secretory cells after intense exocytosis. Microvesicle components that may have a role in envenoming include ecto-5′-nucleotidase, a cell membrane protein that releases adenosine, and aminopeptidase N, a cell membrane protein that may modulate the action of many peptides. Highlights: Small membranous vesicles present in the venom of Crotalus durissus terrificus venom are microvesicles. Microvesicles contain cell membrane proteins (ecto-5′-nucleotidase and aminopeptidase N) and intracellular proteins. Release of microvesicles is a way to regulate the surface of the cells after intense exocytosis during activated stage. Ecto-5′-nucleotidase and aminopeptidase N, plasma membrane proteins, could contribute to the effects of the venom.